Silicone-Based Fouling-Release Coatings for Marine Antifouling - Hu, Peng; Xie, Qingyi; Ma, Chunfeng; Zhang, Guangzhao (Langmuir, 2020)
Marine biofouling profoundly influences marine industries and activities. It slows the speed and increases the fuel consumption of ships, corrodes offshore platforms, and blocks seawater pipelines. The most effective and economical antifouling approach uses coatings. Fouling-release coatings (FRCs) with low surface free energy and high elasticity weakly adhere to marine organisms, so they can be readily removed by the water shear force. FRCs have attracted increasing interest because they are biocide-free and hence ecofriendly. However, traditional silicone-based FRCs have weak adhesion to substrates, low mechanical strength, and low fouling resistance, limiting their applications. In recent years, many attempts have been made to improve their mechanical properties and fouling resistance. This review deals with the progress in the construction of high-performance silicone-based fouling-release surfaces.